Apprenticeship review Lithuania : signposting the apprenticeship path in Lithuania - (:unkn) unknown (Publications Office of the European Union, 2015)
"The publication is the final report of the thematic country review of apprenticeship in Lithuania. The report is based on information and views gathered in consultation with stakeholders in Lithuania (representatives of ministries, social partners, VET providers, companies, students, teachers and trainers). The review took place between May 2014 and March 2015 at the request of the Ministry of Education and Science of Lithuania. The report presents analysis of findings on main features, enablers and challenges of apprenticeship in Lithuanian VET, including the views of stakeholders at different levels. It proposes four directions for action to make apprenticeship a reality in the country: clarifying the vision, building on the enablers, improving information and communication about apprenticeship, and fine-tuning regulation on the way." (Editor, BIBB-Doku)
Keywords: S System beruflicher Bildung; S 2.3 Berufsbildungspolitik; I 2.2.2 Osteuropa; Berufsbildungssystem; Berufsbildungspolitik; Bildungsreform; Litauen